Application of Inter-textual Theory in Teaching Excerpt of the Play "The Spirit of Truong Ba, Skin Butcher" by Luu Quang Vu Under the Competence Development for Students - Anh, Le Hai; Huong, Nguyen Thu (VNU Journal of Science: Education Research; Vol 35 No 3, 2019)
Based on the objectives of the new high school education program as well as the requirements of the modern education environment, this article proposed trends of teaching to apply inter-textual theory to develop students' competences. An excerpt of the play "The Spirit of Truong Ba, the skin of butcher" by Luu Quang Vu is an example for this research.